RELACIÓN ENTRE LA VITAMINA D3 Y LA MORTALIDAD POR COVID-19: ACTUALIZACIÓN - Naranjo Logroño, Ivan Enrique (2022)
Introduction: The world faces a public health emergency due to SARS-CoV-2, which has spread to unusual levels due to its virulence characteristics. Therefore, the associated morbidity and mortality depends on the immune response of the patient. Vitamin D3 is directly related to the immunomodulatory response, acting as a protective factor against risk and aggravation by SARS-CoV-2; since the relationship between vitamin D3 deficiency and acute respiratory distress syndrome and thrombotic episodes has been evidenced. Objective: To carry out a literature review on the relationship between the severity of COVID-19 and vitamin D3 deficiency with mortality derived from this disease. Methodology: A non-systematic bibliographic review is carried out in database sources with current evidence available in PubMed, Cochrane, Science-Direct, Elsevier, Wolters Kluwer, The Lancet, among others. Results: 40 articles in Spanish and English from the last four years are included that meet the defined inclusion criteria and that are requirements of interest for the fulfillment of the objective of the study. Discussion: Vitamin D3 plays an important role in the immune response, increasing the defense capacity of the individual against pathogens through the modulation of the inflammatory response, so its supplementation could be of great benefit against SARS-CoV-2. Conclusions: The anti-inflammatory actions of cholecalciferol decrease the cascade of cytokines that are released, which can significantly improve the symptoms of people infected with COVID-19. However, more research is still needed to corroborate its beneficial effects.